Development cooperation with conflict-affected MENA countries: Refocussing on the social contract - Mark Furness; Annabelle Houdret (Deutsches Institut für Entwicklungspolitik (DIE), 2020)
State-society relations are in flux across the Middle East and North Africa (MENA), nearly a decade after the Arab uprisings. The protests and revolts that swept the region in 2011 arose from widespread rejection of the post-independence Arab social contracts. These were based on redistribution of rents from natural resources and other forms of transfers and subsidies, as "compensation" for acquiescence to political and economic authoritarianism. In several MENA countries, including Iraq, Libya, Syria and Yemen, but also in Algeria, Lebanon and Palestine, the old social contracts have been destroyed by civil conflicts and internationally sponsored wars, which in some cases predated the 2011 uprisings. Since broken social contracts are at the root of conflict in the MENA region, supporting new social contracts should be the core objective of development cooperation with the region's most conflict-affected countries. But "post-conflict reconstruction" often ignores the fact that conflicts do not end with peace agreements, and conflict-affected societies need more than reconstructed infrastructure, institutional capacity and private sector investment if they are to avoid violence in the future. Development agencies term this kind of cooperation "resilience": promoting political, economic, social and environmental stability, rather than risking uncontrollable, revolutionary transformation. However, resilience has often provided cover for short-term measures aimed at preserving the position of particular actors and systems. Development cooperation needs to get beyond reconstruction and resilience approaches that often fail to foster the long-term stability they promise. By focussing on the social contract, development cooperation with conflict-affected countries can provide a crucial link between peacebuilding, reconstruction and longer-term socioeconomic and political development. It can thereby contribute not only to short-term, but also to long-term, sustainable stability. Using the social contract as an analytical lens can increase understanding not only of what donors should avoid doing, but also where they should concentrate their engagement during transitions from civil war. Practical examples from challenging contexts in the MENA region suggest that donors can make positive contributions in support of new social contracts when backing (a) stakeholder dialogues, (b) governance and reforms, and (c) socioeconomic inclusion. In Libya, the socioeconomic dialogue process has brought stakeholders together to outline a new economic vision for the country. The Municipal Development Programme in Palestine focusses on improving the accountability and delivery of local institutions. The Moroccan Economic, Social and Environmental Council provides an example of a process that engages previously marginalised groups. These programmes are all examples of targeted efforts to build cooperation among the groups that make up MENA societies. They aim to broaden decision-making processes, and to increase the impact of specific measures with the ultimate objective of improving state-society relations. They could be adapted for other fragile contexts, with external support. In backing more of these kinds of activities, donors could make stronger contributions to sustainable, long-term peace- and state-building processes in conflict-affected MENA countries.
Keywords: 330; Entwicklungshilfe; Sozialvertrag; Politischer Konflikt; MENA-Staaten; Industrieländer